Empowering Young Ambassadors VocaBoost 2.0 Program on Tioman Island - Zuraina, Ali (UMPSA, 2024)
TIOMAN ISLAND, 22 July 2024 - Tioman Island The VocaBoost 2.0 program, a novel attempt to improve communication skills and environmental awareness, was successfully launched at Sekolah Kebangsaan Tekek, Pulau Tioman.